The regulation of social media influencers - Goanta, Catalina; Ranchordas, Sofia (Elgar law, technology and society., 2020)
"In today's society, the power of someone's reputation, or influence, has been turned into a job: that of being a social media influencer. This role comes with promises, such as aspirational work, but is rife with challenges, given the controversy that often surrounds influencers. This is the first book on the regulation of social media influencers, that brings together legal, economic and ethical angles to further unveil the implications of influencer marketing."